Pengaruh Pertumbuhan Ekonomi, Pengangguran, dan IPM Terhadap Kemiskinan di Provinsi Nusa Tenggara Barat - Widya Widya; Elvira Anisa Fitri; Norma Setiani; Ahmad Ridha; Asnidar Asnidar (Universitas Kristen Indonesia Toraja, 2024)
The aim of this research is to analyze the influence of economic growth, unemployment and the human development index (HDI) on poverty in West Nusa Tenggara Province. The type of research used in this research is quantitative research. Based on the research results, the economic growth variable and the unemployment variable have a positive and insignificant effect on the poverty level. The Human Development Index (HDI) variable has a negative and significant effect on poverty. This means that an increase in HDI by 1% will reduce poverty by 8.38%, with a large or real (significant) reduction in poverty. Simultaneously, the influence variables of economic growth, unemployment, and the human development index influence poverty in West Nusa Tenggara Province.